Pengaruh Total Aset, Dana Pihak Ketiga Dan Financing To Deposit Ratio Terhadap Profitabilitas Pada Bank Umum Syariah - Laila Widya Sari; Annisa Annisa (Politeknik Negeri Padang, 2023)
This study aims to determine the effect of total assets, third party funds and financing to deposit ratio on profitability. With the purposive sampling technique, the population was sampled with a total sample of 8 Islamic commercial banks in 2015-2020. The analytical method used is the panel regression model. The results showed that total assets had a negative and significant effect on profitability, while third party funds and financing to deposit ratios had no effect on profitability.